The relationship of creative leadership with crisis management for the secondary stage in public schools in Jeddah from the teachers’ point of view - Al-Juhani, Hanaa Ebrahim Semran; Hariri, Randa (Journal of Educational and Psychological Sciences, 2021)
The study aimed to discover the relationship between practicing creative leadership and school management crisis among female educational leaders of publicsecondary schools in Jeddah from the latter’s’ perspectives. The study adopted adescriptive, correlational-relational research design and used a questionnaire to randomly collect data from a sample of (357) female teachers during the first semester of the 1441/1442AH academic year. Findings revealed that female school leaders practice creative leadership, and school crisis management at a high degree, whereby, accommodation and cooperation styles ranked first and second respectively, and avoidance style ranked last. Findings also showed that there were statistically significant differences at the level of (0.5 = α) between the means of the degree of creative leadership and crisis management practices referred to the difference in experience. Moreover, results showed a positive correlation between the degree of creative leadership and crises management practices. The study recommended holding events in the education and schools’ management that highlight the role of creative leadership and its impact on enhancing schools’ ability to manage and face crises, along with offering training courses aboutcrisis management, and encouraging relevant practices by teachers and staff members.